Head Orthosis Therapy in Positional Plagiocephaly: Influence of Age and Severity of Asymmetry on Effect and Duration of Therapy. Issue 2 (August 2017) - Kunz, Felix; Schweitzer, Tilmann; Kunz, Jessica; Waßmuth, Nina; Stellzig-Eisenhauer, Angelika; Böhm, Hartmut; Meyer-Marcotty, Philipp; Linz, Christian
Abstract : Background: Only a few studies investigating the optimal time point at which to start orthotic treatment for deformational plagiocephaly take into account the severity of skull asymmetry. The present study performs a three-dimensional analysis of the effects of age and severity of asymmetry on the final outcome. Methods: A total of 144 patients with deformational plagiocephaly treated by molding orthosis were examined and divided into three age groups (group I, <24 weeks; group II, ≥24 to <32 weeks; and group III, ≥32 weeks) and two severity levels (mild to moderate, 30-degree cranial vault asymmetry ≥3 mm to ⩽12 mm; and moderate to severe, 30-degree cranial vault asymmetry >12 mm). The extent of the reduction of asymmetry was analyzed using three-dimensional stereophotogrammetry. Results: Therapy with molding orthosis led to a significant reduction in asymmetry in all defined age groups. Efficacy of reduction decreased with increasing age. Successful treatment (cranial vault asymmetry index <3.5 percent) was achieved in 83, 69, and 40 percent of patients with mild to moderate asymmetry in groups I, II, and III, respectively; and in 50, 30, and 7 percent of patients with moderate to severe asymmetry in groups I, II, and III, respectively. The average duration of treatment increased from 18.6 weeks to 25.3 weeks (age groups I and III). Conclusion: Age at the beginning of treatment and severity of asymmetry have a definite impact on the duration and effectiveness of molding orthosis therapy. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, II.